Hydroxyl-Substituted Ladder Polyethers via Selective Tandem Epoxidation/Cyclization Sequence - Czabaniuk, Lara C. (Org Lett, 2015)
[Image: see text] A new and highly selective method for the synthesis of hydroxyl-substituted tetrahydropyrans is described. This method utilizes titanium(IV) iso-propoxide and diethyl tartrate to perform a diastereoselective epoxidation followed by in situ epoxide activation and highly selective endo-cyclization to form the desired tetrahydropyran ring. The HIJ ring fragment of the marine ladder polyether yessotoxin was synthesized using this two-stage tactic that proceeds with high efficiency and excellent regioselectivity.